2021
DOI: 10.3390/pollutants1040020
|View full text |Cite
|
Sign up to set email alerts
|

Use of Clay Minerals to Control Radioactive Cesium Leaching from Municipal Solid Waste Incineration Ash in Fukushima Prefecture in Summer and Winter

Abstract: Radioactive cesium (r-Cs) released from the 2011 Fukushima Daiichi Nuclear Power Plant attaches to vegetation/soil and is collected as municipal solid waste (MSW) for incineration, being concentrated in incineration ash (bottom ash [BA], fly ash [FA], and chelate-treated FA [TFA]). r-Cs in FA and TFA can easily leach upon contact with moisture. It is important to prevent further contamination, as r-Cs has negative effects on ecosystems and the human body. Naturally available clay minerals, considered effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
(45 reference statements)
0
1
0
Order By: Relevance
“…Murasawa N [6] found that the addition of clay minerals can effectively inhibit the leaching of radioactive cesium (r-Cs) in the incineration process of municipal solid waste, especially for fly ash (FA) and chelate treatment of FA (TFA). This study provides important experimental basis and technical support for reducing radioactive material contamination by directly adding and mixing clay minerals into waste ash.…”
Section: Relevant Researchmentioning
confidence: 99%
“…Murasawa N [6] found that the addition of clay minerals can effectively inhibit the leaching of radioactive cesium (r-Cs) in the incineration process of municipal solid waste, especially for fly ash (FA) and chelate treatment of FA (TFA). This study provides important experimental basis and technical support for reducing radioactive material contamination by directly adding and mixing clay minerals into waste ash.…”
Section: Relevant Researchmentioning
confidence: 99%